Academic burnout and family communication as predictors of life satisfaction in Peruvian university students - Gutierrez Ticona, Julia; Barahona Urbano, Rocío Natalí; Barahona Urbano, Diana Ruth; Turpo-Chaparro, Josue Edison; Conde Rodríguez, Isaac Alex (Frontiers in Education, 2024)
This study aimed to determine if academic burnout and family communication predict life satisfaction in Peruvian university students. The design was cross-sectional predictive, and 708 Peruvian university students participated. The Maslach Burnout Inventory (MBI), the Family Communication Scale (FCS), and the Satisfaction with Life Scale (SWLS) were used to obtain information on the variables. Descriptive and inferential analysis used structural equation modeling and the Robust Maximum Likelihood Estimator. The results present a negative relationship between Academic Burnout and Life Satisfaction with a significant estimate of -0.849 (p < 0.001), with a beta coefficient (β) of -0.469, and a positive relationship between Family Communication and Life Satisfaction, showing a significant positive estimate of 0.436 (p < 0.001), with a beta coefficient (β) of 0.420. These results confirm the need to implement programs that provide guidance to students on academic burnout and how to prevent it. Likewise, strategies to improve family communication must be incorporated in order to improve students' life satisfaction. In conclusion, these findings confirm that AB and FC are predictive factors of LS, academic Burnout decreases life satisfaction, and family communication increases life satisfaction in Peruvian university students.